Counter-Mapping Maroon Cartographies: GIS and Anticolonial Modeling in St. Croix - Dunnavant, Justin P.; Wernke, Steven A.; Kohut, Lauren E. (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Formal spatial modeling and analytical approaches to maroon settlement, fugitivity, and warfare in the colonial-era Caribbean have tended to mine historical cartographic sources instrumentally to analyze the distributions and simulate processes driving marronage in St. Croix (Dunnavant 2021b; Ejstrud 2008; Norton and Espenshade, 2007). Through close-in analysis, we compare two Danish maps of St. Croix produced in 1750 and 1799 in relation to modern cartographic sources, to explore how cartographic forms and cartesian conventions (attempt to) elide blind spots in the colonial gaze. By modeling possible subject-oriented maroon movement on georeferenced colonial maps and contemporary LiDAR, we demonstrate how GIS can recover anti-colonial agency. Additionally, the practice of georeferencing itself is a critical site of analysis, revealing distortions suggestive of social and environmental conditions that limited colonial cartographers’ ability to map certain wilderness and contested landscapes that lay outside of their control.